2005
DOI: 10.1111/j.1600-0447.2005.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity among individuals with serious mental illness

Abstract: Obesity is more prevalent among individuals with serious mental illness than in demographically matched individuals from the US general population. Among persons with mental illness, obesity is associated with co-occurring health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 30 publications
3
142
2
1
Order By: Relevance
“…To our knowledge, this is the first time that the nutritional status In-patient Out-patient All of psychiatric inpatients and outpatients has been assessed in a Malawian mental health facility. Elsewhere, studies have shown that obesity is higher among schizophrenic patients than in the general population 10,11 . Overnutrition and obesity in individuals with mental disorders such as schizophrenia has been attributed to factors such as sedentary lifestyle, poor nutritional choices or lack of access to healthy foods, the effects of both the mental disorder itself and the medications used to treat it, and lack of access to adequate preventative medical care 12 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first time that the nutritional status In-patient Out-patient All of psychiatric inpatients and outpatients has been assessed in a Malawian mental health facility. Elsewhere, studies have shown that obesity is higher among schizophrenic patients than in the general population 10,11 . Overnutrition and obesity in individuals with mental disorders such as schizophrenia has been attributed to factors such as sedentary lifestyle, poor nutritional choices or lack of access to healthy foods, the effects of both the mental disorder itself and the medications used to treat it, and lack of access to adequate preventative medical care 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Population with a psychiatric disorder is at higher risk for overweight and obesity than healthy ones [18][19][20]. At present there is no clear link concluded between obesity and psychopathology, and whether the possible psychological disorders are a cause or a consequence of obesity has not yet been clarified either [21].…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее частая комбинация -абдоминаль-ное ожирение, диабет II типа и артериальная ги-пертензия встречается у 20-25% всего взрослого населения планеты [5]. Установлено, что пациен-ты с психотическими расстройствами в два раза чаще страдают от ожирения, чем представители общей популяции [6]. Пациенты с тяжелыми пси-хическими расстройствами, такими как шизоф-рения, еще больше подвержены риску за счет вредных привычек, часто регистрированных в их анамнезе -курение, алкогольная зависимость, малоподвижный образ жизни [7].…”
Section: антипсихотик-индуцированный метаболический синдромunclassified